Is it feasible to establish a connection between cassava and rice in terms of their image? - Yuniwati, Eny Dyah; Darmayanti, Rani; Karim, Samuel (CV. Bimbingan Belajar Assyfa, 2023)
Cassava can be consumed through various processing methods, including boiling, frying, grilling over wood charcoal, and pounding and processing into a starchy paste known as getup. During its day, this tradition exhibited qualities that were commendable, pragmatic, and held significant worth. Nevertheless, successfully adopting these preparations and cuisines among the millennial age and age Z necessitates ingenuity and inventiveness. This study investigates the potential of cassava rice as a viable alternative to paddy rice while also proposing strategies to enhance the reputation and market perception of cassava rice to match that of paddy rice objects. The researchers employed a systematic literature review methodology, which was subsequently followed by a comprehensive analysis and comparison of the data put forth in earlier investigations. The findings of the study indicate that cassava rice has the potential to serve as a viable alternative to traditional rice on a national scale. Hence, cassava rice can be analogous to regular rice due to its significant carbohydrate content, allowing it to fulfill the same dietary role. The primary objective of this research is to establish a foundation for micro companies to conduct experimental trials in order to substantiate the advantages of cassava rice, both in terms of its nutritional value and its potential for use in various recipes. The research is constrained by its methodology, which relies on longitudinal and laboratory findings as the theoretical foundation.